CkREV regulates xylem vessel development in Caragana korshinskii in response to drought - Li, Jiayang; Xie, Lifang; Ren, Jiejie; Zhang, Tianxin; Cui, Jinhao; Bao, Zhulatai; Zhou, Wenfei; Bai, Juan; Gong, Chunmei (Frontiers in Plant Science, 2022)
Drought stress poses severe threat to the development and even the survival status of plants. Plants utilize various methods responding to drought, among which the forming of more well-developed xylem in leaf vein in woody plants deserves our attention. Herein, we report a transcription factor CkREV from HD-ZIP III family in Caragana korshinskii, which possesses significant functions in drought response by regulating xylem vessel development in leaf vein. Research reveal that in C. korshinskii the expression level of CkREV located in xylem vessel and adjacent cells will increase as the level of drought intensifies, and can directly induce the expression of CkLAX3, CkVND6, CkVND7, and CkPAL4 by binding to their promoter regions. In Arabidopsis thaliana, CkREV senses changes in drought stress signals and bidirectionally regulates the expression of related genes to control auxin polar transport, vessel differentiation, and synthesis of cell wall deposits, thereby significantly enhancing plant drought tolerance. In conclusion, our findings offer a novel understanding of the regulation of CkREV, a determinant of leaf adaxial side, on the secondary development of xylem vessels in leaf vein to enhance stress tolerance in woody plants.